3w-1=6w-5

Simple and best practice solution for 3w-1=6w-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w-1=6w-5 equation:


Simplifying
3w + -1 = 6w + -5

Reorder the terms:
-1 + 3w = 6w + -5

Reorder the terms:
-1 + 3w = -5 + 6w

Solving
-1 + 3w = -5 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
-1 + 3w + -6w = -5 + 6w + -6w

Combine like terms: 3w + -6w = -3w
-1 + -3w = -5 + 6w + -6w

Combine like terms: 6w + -6w = 0
-1 + -3w = -5 + 0
-1 + -3w = -5

Add '1' to each side of the equation.
-1 + 1 + -3w = -5 + 1

Combine like terms: -1 + 1 = 0
0 + -3w = -5 + 1
-3w = -5 + 1

Combine like terms: -5 + 1 = -4
-3w = -4

Divide each side by '-3'.
w = 1.333333333

Simplifying
w = 1.333333333

See similar equations:

| .5(4x+4)-(x-8)= | | 7(9+4x)=-105 | | 7x^2+.5x=0 | | 2(9)+(3)= | | 28=3(1+x)+5(-x+5) | | 8+5x=52x | | x^12*x-8=0 | | 2x^2+88=(2x+4)(x+4) | | 2x^2+88=2x^2+12x+8 | | 6m-2y=3y-2 | | 2+3(-6+4)=8 | | n+10-6=7 | | 4(v+4)-7v=-14 | | M-7m-9m+2= | | y=-5x+16 | | -h-24=5-h | | 10t-5t^2=2 | | 21-2(3)= | | 0.3-0.625=0.875 | | 2x+1y=36 | | 6x^2+90x+324=0 | | 3y+2-2y-5=-4y-3 | | 16b=40-4b | | 3y+2-2y-5=-4x-3 | | e=mc(2) | | -7(6-x)-5x=-24+5x | | 10x-6=10+6x | | 0.16(12)+0.04x=0.08(24+x) | | 3y+2-2y-5=-2x-2 | | (2x+1)+(4-3x)=10 | | 7z-10-z+4=0 | | x+2*x+2*x+2*x+2+11=49 |

Equations solver categories